The Philosophy of Trans-Historic-History Followed by President López Obrador - Ortiz Delgado, Francisco Miguel (2023)
The writings and speeches of the Mexican president Andrés Manuel López Obrador (2018-2024) have been characterized by a constant reference to a teleological history. Using Karl Löwith’s proposals, I analyse the president’s liberal-progressive idea of history and I propose that in this respect he has followed a certain speculative philosophy of history, which I call philosophy of Trans-Historic-History.